Versatile C(sp2)−C(sp3) ligand couplings of sulfoxides for the enantioselective synthesis of diarylalkanes - Dean, William Michael; Mindaugas, Šiaučiulis; Storr, Thomas E.; Lewis, William; Stockman, Robert A. (Wiley-VCH Verlag, 2016)
The reaction of chiral (hetero)aryl benzyl sulfoxides with Grignard reagents affords enantiomerically pure diarylalkanes in up to 98% yield and greater than 99.5% enantiomeric excess. This ligand coupling reaction is tolerant to multiple substitution patterns and provides access to diverse areas of chemical space in three operationally simple steps from commercially available reagents. This strategy provides orthogonal access to electron-deficient heteroaromatic compounds, traditionally synthesised via transition metal-catalysed cross-couplings, which circumvents common issues associated with proto-demetalation and β-hydride elimination.